Air quality in urban environments - Hester,R.E; Harrison,R.M; Hester, R. E.; Harrison, Roy M. (Cambridge, UK : RSC Publishing, 2009)
This comprehensive volume deals with the basic science of urban air pollution in relation to the sources and concentrations, and the atmospheric chemical and physical processes which determine those concentrations and lead to the formation of secondary pollutants by chemical reactions in the atmosphere--
Keywords: Air; Urban pollution; Air quality management; Air